2017
DOI: 10.1097/md.0000000000007961
|View full text |Cite
|
Sign up to set email alerts
|

Readmission due to infection following total hip and total knee procedures

Abstract: Policymakers have expanded readmissions penalty programs to include elective arthroplasties, but little is known about the risk factors for readmissions following these procedures. We hypothesized that infections after total hip arthroplasty (THA) and total knee arthroplasty (TKA) lead to excess readmissions and increased costs. This study aims to evaluate the proportion of readmissions due to infections following THA and TKA.Healthcare Cost and Utilization Project–State Inpatient Databases were used for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 12 publications
(14 reference statements)
1
24
0
2
Order By: Relevance
“…Gáspár et al 10 suggested that pre‐ and post‐operative pain in osteoarthritis is not correlated with the density of nerve fibers found in the capsule. Some authors have reported better post‐operative satisfaction (Harris Hip Score) in cases in which the capsule was preserved and repaired, with respect to cases in which the capsule was removed, but this difference disappeared 6 months post‐operatively 12 . The ligamentum teres also seems to play a role as a pain generator and joint lubricator 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Gáspár et al 10 suggested that pre‐ and post‐operative pain in osteoarthritis is not correlated with the density of nerve fibers found in the capsule. Some authors have reported better post‐operative satisfaction (Harris Hip Score) in cases in which the capsule was preserved and repaired, with respect to cases in which the capsule was removed, but this difference disappeared 6 months post‐operatively 12 . The ligamentum teres also seems to play a role as a pain generator and joint lubricator 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…In California (from 2009 to 2011), 4.29% of patients were readmitted with 33.02% recorded readmissions due to infection 65 . In Florida (from 2009 to 2013), 4.7% of patients were readmitted with 33.39% of patients diagnosed with septic arthritis 65 .…”
Section: Length Of Hospital Stay and Early Readmissions Due To Infectionmentioning
confidence: 99%
“…In California (from 2009 to 2011), 4.29% of patients were readmitted with 33.02% recorded readmissions due to infection 65 . In Florida (from 2009 to 2013), 4.7% of patients were readmitted with 33.39% of patients diagnosed with septic arthritis 65 . In Massachusetts (from 2010 to 2012), 3.92% of patients were readmitted with 35.2% for periprosthetic joint infection 65 .…”
Section: Length Of Hospital Stay and Early Readmissions Due To Infectionmentioning
confidence: 99%
See 2 more Smart Citations